DBP rs7041 and DHCR7 rs3829251 are Linked to CD4+ Recovery in HIV Patients on Antiretroviral Therapy - Resino, Salvador; Jiménez-Sousa, María Ángeles; Blanco, Julià; Pacheco, Yolanda M.; del Romero, Jorge; Peraire, Joaquim; Virseda-Berdices, Ana; Muñoz-Gómez, María José; Galera-Peñaranda, Carlos; García-Fraile, Lucio Jesus; Benito, José M.; Rallón, Norma (Frontiers in Pharmacology, 2022)
Background: The lack of the recovery of CD4+ T-cells (CD4+ recovery) among immunodeficiency virus (HIV)-infected patients on antiretroviral therapy (ART) is not well known. We aimed to analyze the association between single nucleotide polymorphisms (SNPs) underlying vitamin D metabolism and the CD4+ recovery in naïve HIV-infected patients who started ART with low baseline CD4+. Methods: We conducted a retrospective study in 411 naïve individuals with plasma HIV load >200 copies/mL and CD4+ <200 cells/mm3. During 24 months of follow-up, all patients had plasma HIV load <50 copies/mL. DNA genotyping was performed using the Sequenom MassARRAY platform. The outcome variable was the change in CD4+ during the study. Results: CD4+ recovery was higher in patients carrying DBP rs7041 AA genotype (AA versus CC/AC) and DHCR7 rs3829251 AA genotype (AA versus GG/AG) (p-value <0.05). DBP rs7041 AA genotype was linked to increase in CD4+ (adjusted arithmetic mean ratio (aAMR)=1.22; q-value=0.011), increase in CD4+ ≥P75th (adjusted odds ratio (aOR)=2.31; q-value=0.005), slope of CD4+ recovery (aAMR=1.25; q-value=0.008), slope of CD4+ recovery ≥P75th (aOR=2.55; q-value=0.005) and achievement of CD4+ ≥500 cells/mm3 (aOR=1.89; q-value=0.023). Besides, DHCR7 rs3829251 AA genotype was related to increase in CD4+ (aAMR=1.43; q-value=0.031), increase in CD4+ ≥P75th (aOR=3.92; q-value=0.030), slope of CD4+ recovery (aAMR=1.40; q-value=0.036), slope of CD4+ recovery ≥P75th (aOR=3.42; q-value=0.031) and achievement of CD4+ ≥500 cells/mm3 (aOR=5.68; q-value=0.015). Conclusion: In summary, DHCR7 rs3829251 and DBP rs7041 polymorphisms were associated with CD4+ recovery in HIV-infected patients who started cART with low CD4+ T-cell counts.